Degradation of air pollutants from waste burning using photocatalyst TiO2 with Co(NO3)2 doped under ultraviolet irradiation - Munna , Kamila; Aflaha , Rizky; Chotimah , Chotimah (Greensusmater, 2024)
Air pollutants, such as carbon dioxide (CO2), hydrogen cyanide (HCN), and methane (CH4), can harm the respiratory organs of humans and cause several diseases. This study successfully utilized a photocatalyst from TiO2 with Co(NO3)2 doped to degrade these air pollutants from waste burning. The photocatalyst layer was produced by dissolving TiO2 and Co(NO3)2 in distilled water, and then the solution was coated on a mica surface using a spray coating method. The coated mica was then dried in an oven. The crystallite structure of TiO2/Co(NO3)2 was analyzed by X-ray diffraction. The obtained crystallite size was (15.38 ± 0.03) nm with lattice parameters a and c were (3.8 ± 0.3) Å and (9.3 ± 0.3) Å, respectively, which shows that it is an anatase phase. The band gap energy was measured by diffuse reflectance UV-visible spectroscopy and analyzed by Tauc's plot method. The measured band gap energy of the photocatalyst was 2.81 eV, which can be easily activated by ultraviolet (UV) light. The photocatalyst sheets successfully degraded air pollutants from waste burning, including 53.139% CO2 for 4 hours, 100% HCN for 10 minutes, and 72.381% CH4 for 40 minutes. Therefore, the fabricated photocatalyst in this study can potentially be an alternative to degrading air pollutants, especially CO2, HCN, and CH4.